Sustainability and risk management. Response, repair and prevention against floods from a case analysis - Carrizo Sineiro, Cecilia (2018)
The province of Córdoba is one of the poles of development of the agricultural model based on transgenic-agrotoxicos-direct seeding-commodities implemented in Argentina. It is located in the region for which the Intergovernmental Panel on Climate Change (IPCC) has forecast more than 10 years ago the occurrence of extreme rainfall, consequent floods and specific adaptation needs. The work aims to problematize the limits of risk management in this context from the analysis of a specific case, the city of Jesus Maria after the flood of 2015. To this end, we present in detail the systematization of actions of two urban social systems identified as key, the Institutional Political System and the Information-Communication System, in the three moments in which disasters are analyzed: response, repair and prevention. Our observation, from a systemic-communicational perspective, aims to increase social reflexivity on a production model, accounting for the complexity of a grammar of adaptation to climate change, focusing on private and public responsibilities and the defense of human rights, biodiversity and public and private infrastructure, overcomes inefficient and technocratic responses and prefigures an adaptation to climate change that focuses on sustainability.